1992
DOI: 10.1002/1097-0142(19921101)70:9<2268::aid-cncr2820700910>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor immunoreactivity in pancreatic endocrine tumors. An immunocytochemical study of 156 neuroendocrine tumors of the pancreas, gastrointestinal and respiratory tracts, and skin

Abstract: Background. The immunoreactivity for progesterone receptors (PR) of the majority of endocrine cells of the human pancreas has prompted the authors to investigate if PR expression is maintained in pancreatic endocrine tumors and is correlated with the main clinicopathologic features of these neoplasms. Furthermore, the study has been extended to other neuroendocrine cells and tumors to determine whether PR immunoreactivity is a common feature of neuroendocrine cells and tumors other than those of the pancreas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 44 publications
6
39
1
Order By: Relevance
“…Normal islet cells express progesterone receptors and CD 99, and about half of PENs label for these markers as well. 9,41,42 Proliferation markers such as Ki67 are expressed in less than 10% of the neoplastic cells, and in most cases the rate is between 5% and less than 1%. 1,4,14,43 Genetic studies have identified many chromosomal alterations in PENs; however, activation of oncogenes has not been implicated in their development.…”
Section: Pancreatic Endocrine Neoplasmssupporting
confidence: 77%
See 1 more Smart Citation
“…Normal islet cells express progesterone receptors and CD 99, and about half of PENs label for these markers as well. 9,41,42 Proliferation markers such as Ki67 are expressed in less than 10% of the neoplastic cells, and in most cases the rate is between 5% and less than 1%. 1,4,14,43 Genetic studies have identified many chromosomal alterations in PENs; however, activation of oncogenes has not been implicated in their development.…”
Section: Pancreatic Endocrine Neoplasmssupporting
confidence: 77%
“…9 Nuclear pleomorphism is also not a useful predictor, 30 although some studies have demonstrated a correlation between overall nuclear grade and prognosis. 9 Other factors reportedly predictive of more aggressive behavior (at least in univariate analyses) include loss of progesterone receptor expression, 42,43 aneuploidy, 70,71 increased Ki67 labeling index, 43,72 loss of heterozygosity (LOH) of chromosome 17p13, 20 LOH of chromosome 22q, 73 increased fractional allelic loss, 74 upregulated CD44 isoform expression, 75,76 and immunohistochemical expression of cytokeratin 19. 77 A number of grading schemes have been proposed for PENs, including some that attempt to separate them into benign and malignant groups as well as others that simply stratify the risk for recurrence.…”
Section: Pancreatic Endocrine Neoplasmsmentioning
confidence: 99%
“…Interestingly, they are also expressed in the brain, bone, pancreas, testes, and lower urinary tract (Viale et al, 1992;Clarke, 1997, 2002;Bland, 2000;Han et al, 2009;Tincello et al, 2009). Examination of the phenotype of PR-null animals has provided significant insight into the explicit functions of the two PR isoforms.…”
Section: B Progesterone Receptor Functionmentioning
confidence: 99%
“…There have been a limited number of studies characterising the steroid hormone receptor profile of pancreatic tumours. PRs have been detected immunohistochemically in normal pancreas and pancreatic tumours, almost exclusively being confined to endocrine pancreas tissue (Doglioni et al 1990, Viale et al 1992. A decade ago, oestrogen receptor (ER) presence was demonstrated in pancreatic tumour tissue using radioligand binding assays and Scatchard analysis (Greenway et al 1981).…”
Section: Introductionmentioning
confidence: 99%